Da democracia racial à ação afirmativa : o caso da Universidade Estadual do Norte Fluminense - Matta, Ludmila Gonçalves da (2007)
The affirmative action in a recent initiative in the Brszilian universities and, in this context, the universities of Rio de Janeiro, Uenf and Uerj, which were the pioneers, reserving 50% of the vacancies initially for students of public schools and, later, extending the list of the quotas for blacks and brown, not making distinction among them, reserving 40% of the vacancies for them. This dissertation hás as objective to evaluate the process of implementation of the politics of quotas in the Universidade Estadual do Norte Fluminense, as well as to deepen the debate about the theme. The research evaluates the process starting from the results of the vestibular (college entrance) exam, the students performance and the social relationships in the academic atmosphere.